2002
DOI: 10.1017/s0003598x0009044x
|View full text |Cite
|
Sign up to set email alerts
|

The chronology of the Mariupol-type cemeteries of Ukraine re-visited

Abstract: Recent results of radiocarbon analyses from sites in Ukraine suggest that a revision of the chronology of the Late mesolithic and early Neolithic is required. The subsequent Neolithic period up to the beginning of the Early Bronze Age (c.3000 cal BC) should be divided into two separate periods, the Neolithic and Neo-eneolithic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 8 publications
0
26
1
Order By: Relevance
“…However, it should be noted that, in failing to account for the probability that the remains represent different population groups from different periods, when comparing the Verteba remains to the earlier prehistoric (Mesolithic and Neolithic) populations interred in the Dnieper-Donets Mariupol-type cemeteries along the Dnieper and its tributaries (Lillie 1996;Potekhina 1998;1999;Telegin et al 2002;2003), these authors erroneously conclude that significantly shorter bone lengths, in addition to higher rates of enamel hypoplasias (which are non-specific indicators of stress; Goodman et al 1984;Goodman, Rose 1991) suggest that the Trypillian farming lifestyle was more stressful in terms of physiological perturbations when contrasted with the hunter-fisher-foragers of the Dnieper Rapids region. Given the fact that the earlier Mesolithic and Neolithic DnieperDonets populations were tall, with massive skeletons and very wide faces (with two variants in evidencedolichocrany and mesocrany (Potekhina 1998)), and that Inna Potekhina (1998.67-68;1999;also Telegin et al 2002;2003) has shown that the DnieperDonets populations differed markedly from the Trypillia, Sredny Stog and Kemi-Oba populations, with Trypillia populations being of smaller stature and more gracile, it is apparent that using long-bone lengths as a measure of population stress between groups that are distinct in both anthropological and chronological terms is a fundamentally flawed approach.…”
Section: The Trypillian Culture and Verteba Cavementioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that, in failing to account for the probability that the remains represent different population groups from different periods, when comparing the Verteba remains to the earlier prehistoric (Mesolithic and Neolithic) populations interred in the Dnieper-Donets Mariupol-type cemeteries along the Dnieper and its tributaries (Lillie 1996;Potekhina 1998;1999;Telegin et al 2002;2003), these authors erroneously conclude that significantly shorter bone lengths, in addition to higher rates of enamel hypoplasias (which are non-specific indicators of stress; Goodman et al 1984;Goodman, Rose 1991) suggest that the Trypillian farming lifestyle was more stressful in terms of physiological perturbations when contrasted with the hunter-fisher-foragers of the Dnieper Rapids region. Given the fact that the earlier Mesolithic and Neolithic DnieperDonets populations were tall, with massive skeletons and very wide faces (with two variants in evidencedolichocrany and mesocrany (Potekhina 1998)), and that Inna Potekhina (1998.67-68;1999;also Telegin et al 2002;2003) has shown that the DnieperDonets populations differed markedly from the Trypillia, Sredny Stog and Kemi-Oba populations, with Trypillia populations being of smaller stature and more gracile, it is apparent that using long-bone lengths as a measure of population stress between groups that are distinct in both anthropological and chronological terms is a fundamentally flawed approach.…”
Section: The Trypillian Culture and Verteba Cavementioning
confidence: 99%
“…This is clearly unsatisfactory, as previous work has shown that relative chronologies can have considerable discrepancies when compared to absolute chronologies (e.g., Telegin et al 2002;2003), and alongside these observations, the importance of the absolute dating of Verteba's burials can perhaps be further emphasised by noting that, despite the occurrence of over 1000 Trypillia settlement sites from c. 5400 cal BC onwards, skeletal remains and burials that date to the period before CII (pre-3400 cal BC) are almost unknown (Kruts 2008;Korvin-Pietrovskiy 2012).…”
mentioning
confidence: 92%
“…This means that even a few shards of pottery discovered in a Mesolithic fisherman-huntergatherer camp identifies the site as one of Neolithic pottery-using fishermen-hunter-gatherers, regardless of the changes in society (cf. Telegin et al 2002). This approach is justified by noting that many regions of Eastern and northern Europe emerged as food-producing economies only in the Early Bronze Age, and that if we were to link the Neolithic period with the begin-GIEDRĖ MOTUZAITĖ MATUZEVIČIŪTĖ N e o l i t h i c U k r a i n e : a R e v i e w o f T h e o r e t i c a l a n d C h r o n ol o g i c a l I n t e r p r e t a t i o n s ning of food production in these societies 'we would be obliged to agree that there was no Neolithic at all at this vast territory' (Zhilin 2000, p.287 Dolukhanov et al 2005).…”
Section: Baltica 20 II N E O L I T H I C I N E a S T E R N E U R O P Ementioning
confidence: 99%
“…The deceased were placed in collective pits, where bodies were stretched out on their backs (Telegin 1985a, p.158), or in a supine position (Telegin et al 2003, p.466), with boar, deer and fish tooth ornaments and ochre as grave goods (Telegin 1986). The inhabitants were tall, widefaced and dolichocranic (Jacobs 1994a;Jacobs 1994b;Potekhina 1998;Potekhina, Telegin 1995;Telegin 1985a;Telegin et al 2002). There are two interpretations of the origins of the cultures in this region.…”
Section: Giedrė Motuzaitė Matuzevičiūtė N E O L I T H I C U K R a I Nmentioning
confidence: 99%
See 1 more Smart Citation